Effects of clonazepam and flunitrazepam on the development cycle of Calliphora vicina Robineau-Desvoidy 1830 and their forensic implications - Lavinia Iancu; Malia Wellens; Tiberiu Sahlean (Scientific Reports)
Abstract Benzodiazepines are commonly identified in drug overdose deaths worldwide. However, research on their effects on the most common necrophagous insect species is limited. In this context, the current study investigated the effects of clonazepam and flunitrazepam on the development cycle of Calliphora vicina Robineau-Desvoidy, 1830 (Diptera: Calliphoridae). Three blow fly colonies were reared under controlled laboratory conditions (24℃, 50% humidity, 12:12 light-dark cycle), and the experiment was carried out in triplicate. A solution of 4 mg of clonazepam and 2 mg of flunitrazepam, each dissolved in 50 mL of ultrapure water, was added to minced beef liver. The development cycle and growth rate were monitored daily, with a total of 2700 specimens weighed, covering each developmental stage except for the egg clusters. Statistical analyses using aligned rank transform (ART) ANOVA revealed significant interactions between the drug and developmental stages. Larvae exposed to benzodiazepines had higher median weights compared to controls, with more pronounced effects observed during the transition from the third instar larvae to the pupae stage. However, no differences were observed regarding the development cycle length between the three colonies. The findings suggest that clonazepam and flunitrazepam influence C. vicina morphology, particularly weight, which, when size is considered, has potential implications for forensic entomology in estimating the minimum postmortem interval (minPMI).